Getúlio Vargas e o desenvolvimento do rádio no país: um estudo do rádio de 1930 a 1945 - Oliveira, Luiz André Ferreira de (2006)
This research aims to study how the radio was used, from 1930 to 1945, by Vargas administration and the dialogue between the Government and radio workers. At that time, radio was ruled and received facilities from government to develop itself technically, commercially and professionally. This study tries to understand how the radio net was developped by radialists and if those workers sufferd any governmental interference. The research also aims to discover in wich way radio workers used to interact with social and political movements and how those happenings were treatened by this media. Our study was based on bibliographic research (books, periodicals, newspapers, sites and data basis) and on interviews with people that worked on the radio on the period 1930-1945. We reached the conclusion that government relashionship with radio was made by buying radio stations, by producing govermental programs and by the firm control of private radio satations.